Territoriality in the tompot blenny Parablennius gattorugine from photographic records. Issue 4 (2nd March 2016) - Naylor, P.; Jacoby, D. M. P.
Abstract : The behaviour of the tompot blenny Parablennius gattorugine was studied from a long‐term underwater photographic record from two sites on the south‐west coast of the U.K. Repeated observations of individually identifiable P. gattorugine during 112 dives revealed that male P. gattorugine may guard eggs in a particular crevice over subsequent breeding seasons, reside in the same location for up to 4 years and recover from injuries received in disputes over territory. Further observations included resident males wiping eggs with greatly expanded anal glands, adult‐type fighting between juveniles and unusual behaviour where a large male manipulated an empty mollusc shell for the attention of two smaller conspecifics.